Juridical Analysis of Default in Building Construction Agreements in Limited Liability Companies in Batam, Indonesia - Aminah, Titik (Enigma in Law, 2024)
Building construction agreements are one of the agreements that often occur in Batam, Indonesia. This agreement is usually carried out by a limited liability company (PT) as a contractor with another party as the project owner. Default is one of the problems that often occurs in building construction agreements. This research aims to analyze the juridical aspects of default in building construction agreements at PT in Batam, Indonesia. This research uses normative juridical research methods. Data was obtained through literature study and interviews with sources who are experts in the fields of law and construction. The research results show that defaults in building construction agreements can occur due to various factors, including errors in carrying out work, delays in completing work, damage to work, and violation of the terms of the agreement. Default in a building construction agreement can cause losses for the injured party. Therefore, there are various efforts that can be made by the aggrieved party to resolve the issue of default, including termination of the agreement, claims for compensation, and demands for work to be reworked.